Sharia Bank Management’s Problems - Widyarini Widyarini; Syamsul Hadi (Journal of Islamic Economics Lariba, 2021)
This paper aims to qualitatively examine the reasons for the insecurity of sharia bank implementation. The study uses descriptive methods of analytics using databases published by Sharia Banks on their web sites. This study concludes that the definition of an akad in Law no. 21/2008 does not conform to the definition of MUI’s fatwa, the use of Wadiah and Mudharabah agreements for funding are potentially dholim. Murabahah financing products are potentially haram, Musyarakah application is not appropriate, Ijarah has the potential to violate fiqh; Ijarah Muntahiyya Bi Al Tamlik provides uncertainness for customers. This paper suggests regulators to change the definition of an akad in Law no. 21/2008, Sharia Bank does not use akad wadiah in funding activities, makes adjustments to mudharabah's share of profit, improves murabahah procedures and pricing, and MUI amends Fatwa no. 27/2002.